2007
DOI: 10.1590/s0365-05962007000100006
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo na infância: características clínicas e epidemiológicas

Abstract: Resumo: FUNDAMENTOS -O vitiligo atinge de 0,5 a 4% da população mundial, e 25% dos casos se iniciam antes dos 10 anos. Embora prevalente, estudos epidemiológicos de vitiligo na infância são raros na literatura brasileira. OBJETIVO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
4
7
0
6
Order By: Relevance
“…As for the type of lesion distribution, vitiligo vulgaris was reported in several studies, 7,9,11,16 except for one, which was conducted with a child population, in which the focal type was the most common. 24 This is probably due to early medical treatment, immediately after the appearance of the first lesion in the child. Similarly to the results of this study, segmental vitiligo showed a low frequency of 5%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the type of lesion distribution, vitiligo vulgaris was reported in several studies, 7,9,11,16 except for one, which was conducted with a child population, in which the focal type was the most common. 24 This is probably due to early medical treatment, immediately after the appearance of the first lesion in the child. Similarly to the results of this study, segmental vitiligo showed a low frequency of 5%.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 This is probably due to the cross-sectional nature of this study; the most appropriate study design to assess lesion progression is longitudinal. On the other hand, a Brazilian study found progression in 37.3% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitiligo acomete todas as raças, ambos os sexos com igual prevalência, e aparece em qualquer idade 2,3 . Estima-se que 1-2% da população mundial seja afetada por essa doença, para a qual não existe cura efetiva 4 .…”
Section: Introductionunclassified
“…Na infân-cia pode acometer áreas como genitália, região glútea e periumbilical (Romiti, Maragno, Arnone, & Takahashi, 2009). Por sua vez, o vitiligo caracteriza-se pelo surgimento de manchas brancas, localizadas ou disseminadas pelo corpo, resultantes da perda do pigmento natural da pele, a melanina (Silva, Gontijo, Pereira, & Ribeiro, 2007). O tratamento médico destas doenças na infância, assim como na dermatite atópica, consiste do uso de emolientes e/ou umectantes, asso-ciados a corticosteroides tópicos, fototerapia e, nos casos mais graves, podem requerer terapia sistêmica com imunossupressores (Romiti et al, 2009;Silva et al, 2007).…”
unclassified